2022
DOI: 10.4187/respcare.09704
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mechanical Insufflation-Exsufflation in Invasively Ventilated Critically Ill Adults

Abstract: Mechanical insufflation-exsufflation (MI-E) is traditionally used in the neuromuscular population. There is growing interest of MI-E use in invasively ventilated critically ill adults. We aimed to map current evidence on MI-E use in invasively ventilated critically ill adults. Two authors independently searched electronic databases MEDLINE, Embase, and CINAHL via the Ovid platform; PROSPERO; Cochrane Library; ISI Web of Science; and International Clinical Trials Registry Platform between January 1990-April 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
(145 reference statements)
1
15
0
Order By: Relevance
“…These contraindications and precautions are listed in the instructions for use of the Clearway 2 [ 15 ] (Breas Medical, Mölnlycke, Sweden) and E70 [ 16 ] (Philips Respironics, Murrysville, PA, USA) and by Swingwood and coworkers [ 17 ].…”
Section: Mechanical Insufflation-exsufflation Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…These contraindications and precautions are listed in the instructions for use of the Clearway 2 [ 15 ] (Breas Medical, Mölnlycke, Sweden) and E70 [ 16 ] (Philips Respironics, Murrysville, PA, USA) and by Swingwood and coworkers [ 17 ].…”
Section: Mechanical Insufflation-exsufflation Devicesmentioning
confidence: 99%
“…Interestingly, they reported that clinicians were more likely to use MI-E in the patient without an artificial airway [ 47 ]. Swingwood and colleagues [ 17 ] also reviewed all the papers where MI-E was used in the ICU. From these papers, perceived lack of skills and knowledge and resources were also identified as a barrier; however, they also identified enabling features to utilizing MI-E, in that if they had a positive clinical response to MI-E, then they would be more likely to use it.…”
Section: Barriers To the Use Of Mi-ementioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The interview guide was also informed by previous work and clinical experience of the research group. 12,14,15,21,25 The interview guide (See Table S1) included questions about actual knowledge, skills, environmental context, (inter)professional role and beliefs regarding MI-E in invasively ventilated patients and was reviewed by health care professionals external to the research team prior to use.…”
Section: Data Collectionmentioning
confidence: 99%
“…8,9 It is conventionally used as a non-invasive device with rapid alternation between positivepressure to optimize tidal volume (VT) and lung recruitment followed by negative pressure that augments gas flows, improves sputum mobilization, and ultimately stimulates a cough. 10 Until now, MI-E is used extensively to promote cough and prevent secretion retention in non-critically ill patients, like patients with neuromuscular disease or spinal cord injury, that do or do not receive ventilatory support. 8 Recent intensive care unit (ICU) practice surveys suggest increased use of MI-E as an additional intervention in airway clearance during mechanical ventilation of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%